Cobalt Complexes as an Emerging Class of Catalysts for Homogeneous Hydrogenations - Liu, Weiping; Sahoo, Basudev; Junge, Kathrin; Beller, Matthias (Accounts of chemical research, 2018)
Conspectus Catalytic hydrogenation using molecular hydrogen represents a green and practical approach for reductions of all kinds of organic chemicals. Traditionally, in the majority of these processes the presence of transition metal catalysts is required. In this regard, noble-metal-based catalysts have largely been implemented, such as the application of iridium, palladium, rhodium, ruthenium, and others. Recently, the employment of earth-abundant 3d metals has emerged to replace the utilization of scarce noble metals because of their availability, lower cost, and often reduced toxicity. In this respect, several cobalt complexes, in the form of either molecularly well-defined or in situ-formed complexes, are receiving increasing attention from the scientific community. Importantly, the stability and reactivity of the complexes have greatly been supported by multidentate ligands under steric and/or electronic influences. For instance, tridentate or tetradentate phosphine ligands indirectly tune the reactivity of the metal center to accelerate the overall process, whereas direct participation of the ligand in pincer-type complexes through ligand–metal cooperation regulates the elementary steps in the catalytic cycle. In this Account, we emphasize specifically the advancements in cobalt-catalyzed hydrogenations using molecular hydrogen accomplished in our group. A variety of substrate classes ranging from simple molecules (e.g., carbon dioxide) to complex compounds were explored under the mild and efficient catalytic conditions. Notable examples include the reduction of carbon dioxide to afford either formates using a Co(BF4)2·6H2O/Tetraphos catalyst system or methanol employing a Co(acac)3/Triphos complex in the presence of HNTf2. As interesting examples of the synthesis of fine chemicals, cobalt-promoted hydrogenations of nitriles to primary amines and reductive alkylations of indoles using carboxylic acids as alkylating agents are highlighted. Moreover, highly selective hydrogenations of N-heteroarenes under additive-free conditions were possible by the application of specific cobalt complexes. More recently, a set of carboxylic esters could be hydrogenated to the corresponding alcohols with high efficiency by the use of a well-defined cobalt–PNP pincer catalyst. In particular, the decent reactivity of cobalt catalysts enabled high selectivity and functional group tolerance to be achieved. Throughout our studies, it was found that the pairing of a suitable cobalt precursor and an appropriate tridentate or tetradentate phosphine ligand plays a crucial role harnessing the desired reactivity, while other monodentate and bidentate phosphine ligands showed no reactivity in these investigations. Our developments could provide supervisory information for the future exploration of cobalt-catalyzed hydrogenation reactions and other types of reactions involving cobalt catalysis. Furthermore, relevant contributions from other groups, remaining challenges, and future perspectives in this research area are also presented.